The current status and future needs of global bioaerosol research: a bibliometric analysis - Can-Guven, E. (SPRINGER, 2022)
A bibliometric analysis was conducted to reveal the global status and highlight significant or promising areas of bioaerosol research based on the Web of Science database from 1989 to 2019. Yearly publications, main subject categories, journals, the performance of countries, and research hot topics were identified. The network of keywords and collaborations of countries was visualized and cross relationships were determined. Results showed that the annual output in the field increased during the related period. The USA, China, and Germany are the leading countries while the USA, Germany, and the UK are the most collaborative countries in bioaerosol research. Journal of Aerosol Science is the most productive journal and Environmental Sciences & Ecology is the most popular research area. The research hot spots are health effects, sampling, particulate matter, and indoor air quality in the bioaerosol topic. The findings of this research could provide information to understand the development and trends as well as future needs of bioaerosol research.
Keywords: Aerosol; Indoor air quality; Particulate matter; Research trend; Social network analysis; AEROSOL RESEARCH; EXPOSURE; SCIENCE; PROGRESS; AIR; Environmental Sciences & Ecology